Superabsorbent polymers - An innovative solution for improving water usage efficiency and agriculture productivity - Khoi, Nguyen Van; Tung, Nguyen Thanh; Duc, Nguyen Trung; Ha, Pham Thi Thu; Trang, Pham Thu; Thang, Tran Vu; Huong, Nguyen Thu; Phuong, Nguyen Thi Lien (Vietnam Journal of Science and Technology, 2022)
In recent years, superabsorbent polymers (SAPs) have become an attractive solution to solve the problem of water scarcity in agriculture. This article reviews the literature concerned with preparation techniques of SAPs, methods for evaluating and their application in agriculture. SAPs can be prepared by four main techniques: bulk, solution, inverse suspension and radiation polymerization. Analytical evaluation methods of SAPs, including free absorbency capacity, absorbency under load, swelling rate, swollen gel strength, soluble fraction, residual monomer and ionic sensitivity, are briefly introduced. SAPs have a wide applicability in agriculture. They can be used to efficiently improve water use in agriculture, such as retaining moisture in the soil and reducing irrigation water consumption due to their super high water absorption and water retention capacity. SAPs also have positive impacts on soil properties, such as improving soil as well as improving water and fertilizer efficiency, leading to the enhancement of crop yields.